First records of the genus Macrobathra Meyrick, 1883 (Lepidoptera: Cosmopterigidae) from Taiwan, with description of a new species and two newly recorded species - Lu, Yi-Yang; Liang, Jia-Yuan; Hsu, Yu-Feng (Zootaxa, 2026)
Macrobathra Meyrick, 1883 is a cosmopterigid genus, comprising over 130 species. The present study documents the genus in Taiwan for the first time with two newly recorded species, M. flavidus Qian & Liu, 1997 and M. latipterophora Li & Wang, 2004, and a new species, M. basilutea Lu, Liang & Hsu, sp. nov., is described herein. Images of adults and genitalia of both sexes are provided for the new species, along with a key to the Macrobathra species from Taiwan. DNA barcodes of the three species are provided. A host plant of M. latipterophora, Quercus pachyloma, is also recorded for the first time. Sexual dimorphism is described in M. basilutea sp. nov..